Analisis Puisi “Malam Berdarah” Karya Ozy V. Alandika Menggunakan Pendekatan Mimetik - Isyatul Mardhiah (BADAN PENERBIT STIEPARI PRESS, 2025)
Poetry is a beautiful language expressed in written words based on a person's thoughts and feelings. Poetry is a literary work that is imaginative and contains a similarity in meaning with other uses, so the meaning contained in poetry remains hidden behind words, metaphors, and aesthetics and is conveyed. Not everyone can understand the meaning of poetry. In reading poetry, it is necessary to repeat it several times to understand the meaning of the poem because the language in poetry has a broad, implicit meaning and is difficult to interpret. Therefore, readers must understand how to study poetry with knowledge so that they can understand the meaning of the poetry conveyed. The poem